Inkjet Printing of Long-Range Ordering Two-Dimensional Magnetic Ti0.8Co0.2O2 Film - Yuntian Du; Pengxiang Zhang (Nanomaterials, 2024)
The value of two-dimensional (2D) materials in printed electronics has been gradually explored, and the rheological properties of 2D material dispersions are very different for various printing technologies. Understanding the rheological properties of 2D material dispersions plays a vital role in selecting the optimal manufacturing technology. Inkjet printing is suitable for small nanosheet sizes and low solution viscosity, and it has a significant advantage in developing nanosheet inks because of its masklessness, high efficiency, and high precision. In this work, we selected 2D Ti0.8Co0.2O2 nanosheets, which can be synthesized in large quantities by the liquid phase exfoliation technique; investigated the effects of nanosheet particle size, solution concentration on the rheological properties of the dispersion; and obtained the optimal printing processing method of the dispersion as inkjet printing. The ultrathin Ti0.8Co0.2O2 nanosheet films were prepared by inkjet printing, and their magnetic characteristics were compared with those of Ti0.8Co0.2O2 powder. The films prepared by inkjet printing exhibited long-range ordering, maintaining the nanosheet powders’ paramagnetic characteristics. Our work underscored the potential of inkjet printing as a promising method for fabricating precisely controlled thin films using 2D materials, with applications spanning electronics, sensors, and catalysis.